Humanização da assistência acerca da estimulação das funções orais em lactentes de Lagarto-SE - Morais, Abraão Rabelo de (2019)
Humanization can be defined as the skill to promote a high quality attending joining technological advances with good relationship. Breastfeeding is essential to child health due to its benefits for nutritional, emotional, immunological, social, economic and in child development together with benefits for mother’s health as well. The direct intervention on oral functions consists in repeat stimulation of suction reflex in synchronicity with baby’s. rhythm. The hand smallest finger with glove on is used as a tool to be introduced inside mouth hard palate and in touch with the lower lip to induce baby’s search reflex. However, these exercises must be made before breastfeeding. Therefore, the speech therapist work is active inside maternity hospital supporting the contact between mother and child, feeding, language development and listening. The main objective of this work is to promote the knowledge about oral function stimulation in newly born for postpartum mothers, so children can be correct breastfeed innMaternity Hospital Zacarias Júnior, Lagarto, SE. The methodology is based on descriptive research. It was conducted a descriptive data analysis, quantitative and qualitative, calculating numerical average, standard deviation, absolute frequency and relative frequency. The data from questions (quiz format) answering by the subjects was analyzed by Microsoft Excel. The research was driven in Maternity Hospital Zacarias Júnior, Lagarto, SE. The quiz was applied and organized with semistructured questions at the hospital beds to postpartum mothers who gave birth at this hospital during July until November, 2018. It was chosen thirty subjects and applied thirty quiz. About the results and discussions, nineteen subjects were first son mothers and eleven had two or more previous children. The mothers’ narratives have shown that they received practical orientations on breastfeeding. However, a negative aspect found is the lack of knowledge about oral function stimulation for proper baby feeding. The percentage estimated is about 93, 6%. As the majority of subjects was first born baby mothers and under twenty, the conclusion based on our data and observation is that only a minority has knowledge regarding the importance of oral stimulation for babies. We emphasize the significance of speech therapist participation in the staff of maternity hospitals for orientation on the benefits of oral reflex stimulation for babies.